THE EFFECT OF THE LEARNING MODEL OF GIVING QUESTIONS GETTING ANSWERS AND THINK PAIR SHARE ON MATHEMATICAL LOGICAL INTELLIGENCE - Fitria, Rofiqotul; Pamungkas, Megita Dwi; Hendrastuti, Zuida Ratih (Department of Mathematics Education , University of Jember, 2023)
The objectives of this study are to: (1) analyze the influence of the Giving Question and Getting Answer learning model on the mathematical logical intelligence of grade X students of SMAN 1 Muntilan, (2) analyze the influence of the Think Pair Share learning model on the mathematical logical intelligence of grade X students of SMAN 1 Muntilan, (3) analyze learning models that produce mathematical logical intelligence that is more influential between the Giving Question and Getting Answer learning model or the model Learning Think Pair Share for grade X students of SMAN 1 Muntilan. This type of research is an experiment with a quantitative approach. The population used is tenth grade students of SMAN 1 Muntilan for the 2022/2023 school year. Data collection is done by testing. The tests used are paired sample t-test and independent sample t-test. The results showed that: (1) students' mathematical logical intelligence increased after the application of the giving question getting answer learning model, (2) students' mathematical logical intelligence increased after the implementation of the think pair share learning model, (3) the mathematical logical intelligence of students who were treated with the giving question getting answer learning model was better than students who were treated with the think pair share learning model Keyword: giving question getting answer learning model, mathematical logical intelligence, think pair share learning model.